Choledochal Cysts Resected during Childhood Show No Mutations of KRAS and BRAF as Early Markers of Malignancy in Cholangiocytes - Uecker, Marie; Lehmann, Ulrich; Braubach, Peter; Schukfeh, Nagoud; Madadi-Sanjani, Omid; Ure, Benno M.; Petersen, Claus; Kuebler, Joachim F. (European Journal of Pediatric Surgery, 2020)
Introduction In patients with choledochal cysts (CDC), a hyperplasia-dysplasia-carcinoma sequence can lead to biliary tract malignancy. The limited data available suggest that the risk decreases considerably after excision in childhood. We analyzed samples of resected CDC from pediatric patients histologically and performed mutational analysis of the proto-oncogenes KRAS and BRAF as early markers of malignant alteration in cholangiocytes.Materials and Methods After institutional review board approval, patients undergoing resection for CDC in our center from 2011 to 2019 were retrospectively identified. Histopathological reports were searched for inflammation and endothelial alteration. Cases with sufficient tissue specimen were tested for KRAS codon 12/13 and BRAF codon 600 mutations by pyrosequencing.Results In total, 42 patients underwent resection for choledochal cyst in the study period. Median age at surgery was 2.4 years (range = 18 days–18 years). Histopathological analysis showed no malignancy, but various degrees of inflammation or fibrosis in approximately 50% of the patients and in all age groups. Sufficient tissue for mutation analysis was available for 22 cases, all of which tested negative for KRAS or BRAF mutation.Conclusion In our series, chronic inflammatory changes were frequently present in CDC of infants and children. However, the lack of KRAS and BRAF mutations suggests that no malignant changes have been initiated in this group of European patients undergoing early resection.
Keywords: choledochal cyst; KRAS; BRAF; congenital choledochal malformation